Effect of loading rates and single edge notch bending (SENB) specimen thicknesses on shear lips formation for Al6061 alloy - Abdul Latif, Noradila; Auspan, Afiffikri; Mustapa, Mohammad Sukri; Mohd Joharudin, Nurul Farahin; Nasir, Nurul Fitriah (Microscopy Society of Malaysia, 2019)
Aluminium alloy is a well-known material that has been widely used in automotive industry as automobile parts i.e., car chassis, engine blocks, cylinder heads and pistons. Aluminium 6061 alloy (Al6061 alloy) was used in current study to fulfill the requirement in automotive industry to have a further investigation on the fracture properties of alloy. It was found that the effect of fractured specimen thicknesses on fracture behavior for metallic materials is infrequently investigated under three-point bending test at various loading rates. Investigation on effect of single edge notch bending (SENB) specimen thicknesses on the shear lips ratio of Al6061 alloy is crucial to identify alloy’s behavior under increasing loading rates. Three-point bending test under different loading rates was conducted using different thicknesses of SENB specimen to measure the shear lips ratio on the sides fracture surface of Al6061 alloy. The loading rates of 5, 25 and 50 mm/min, and SENB specimen thicknesses of 10, 15, 20 and 25 mm were performed under three-point bending test. From fractograph of Al6061 alloy, shear lips were formed both sides of notch tip. Shear lips ratio depended on loading rates and SENB specimen thicknesses were determined. Based on the result of analysis, the shear lips ratio was dropped as the thickness of specimen increased and shear lips ratio dropped as the loading rate increased. High loading rate and large thickness of SENB specimen indicated less ductility of alloy due to the less time during plastic deformation for large specimen.